Paul's Agon: Hellenistic Self-Transformation or Judaic Apocalyptic Eschatology in 1 and 2 Thessalonians - Ghisalberti, Giosuè (Philosophy & theology, 2012)
In the letters written to the Thessalonians, Paul’s teaching appears to be irreconcilably divided between a still influential Judaic apocalyptic eschatology and (due to Timothy’s considerable influence in the development of the gospel), an emphasis on Hellenistic self-transformation and, in particular, how the philosophy of Epicurus contributed to the psychological health of recent converts. By interpreting the rhetoric of wrath, quiet, sleep, and childbirth, Paul’s teaching as it emerges in 1 and 2 Thessalonians reveals how the gospel must necessarily encounter, agonistically, two foundations of thought. During the early composition of the letters to his churches, Paul struggles ambivalently between the persistence of a Judaic past and its metaphysical promise of a parousia and eschaton, and the realization that Hellenistic philosophy, and Timothy’s Epicurean pastoral care, provides immediate comfort to the well-being of others.